7x+56-42=x+53

Simple and best practice solution for 7x+56-42=x+53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+56-42=x+53 equation:


Simplifying
7x + 56 + -42 = x + 53

Reorder the terms:
56 + -42 + 7x = x + 53

Combine like terms: 56 + -42 = 14
14 + 7x = x + 53

Reorder the terms:
14 + 7x = 53 + x

Solving
14 + 7x = 53 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
14 + 7x + -1x = 53 + x + -1x

Combine like terms: 7x + -1x = 6x
14 + 6x = 53 + x + -1x

Combine like terms: x + -1x = 0
14 + 6x = 53 + 0
14 + 6x = 53

Add '-14' to each side of the equation.
14 + -14 + 6x = 53 + -14

Combine like terms: 14 + -14 = 0
0 + 6x = 53 + -14
6x = 53 + -14

Combine like terms: 53 + -14 = 39
6x = 39

Divide each side by '6'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| 8(-1+7k)=6(6k+2) | | 4m-6m=6(m-5)+5(4-2m) | | 6(-8)-4(-9)=19 | | 4.28-0.4h=1.48 | | 2(3x-5)-8=-48 | | 12x+7= | | 2p+3-3p+9=10 | | 15x^2+7x+2=0 | | 3.1q-4.6-2.5q=0.4q-4.8 | | 2x+8-4x=-2(x-4) | | 6d-57=7 | | 11X+15X= | | 8f+12=8s+9 | | 3x+13-7x=37 | | -8=.33x+x | | 2y+4y=5 | | -2(1+4n)=3(-n+6) | | -2(-2+3m)+4m=-5(m+1) | | ln(x+12)+ln(x-4)=2lnx | | 7+v(-3)=6+3 | | 4x-4y=48 | | 5x+14-2x=9-4x-2 | | -7x-4=-12-7x | | 12x+12y=48 | | 4=.66x+9-.33x | | 2x^3+4x^2+21x-1=0 | | 2(x-3)=2x-8 | | x-42+16=32-60 | | -5x-13-2x=9(2x-7) | | -15+5x+15=30-50+15 | | -(2+4x)-6x=-2(4x-1) | | -3x+6x-31=44 |

Equations solver categories